Disfungsi Peran Keluarga: Studi Stunting pada Balita di Tanjungpinang Timur, Kota Tanjungpinang, Kepulauan Riau - Novi Gabriella Haria; Jasri Fanny Humairah; Delsy Arya Putri; Vina Oktaviani; Nikodemus Niko (Yayasan Literasi Sains Indonesia, 2023)
This research aims to analyze the relationship between family role dysfunction and stunting among toddlers in East Tanjungpinang, Tanjungpinang City, Riau Islands. Family role dysfunction is one of the potential factors causing stunting in toddlers. Stunting among toddlers is a significant public health issue in Indonesia, particularly in economically disadvantaged and underdeveloped areas. This study employs a qualitative descriptive design. Data were collected through interviews and observations. The research findings indicate the occurrence of family role dysfunction, including the inability to provide attention and support to children, the inability to fulfill the nutritional and health needs of children, and the inability to provide appropriate stimulation and interaction based on the child's age. This study recommends efforts to enhance the family's role in supporting the growth and development of children, particularly in terms of fulfilling the nutritional and health needs of children and providing age-appropriate stimulation. Furthermore, there is a need for health education to raise awareness among the community regarding the importance of the family's role in supporting child growth and development. By doing so, it can enhance public awareness in addressing stunting issues among toddlers in East Tanjungpinang, Tanjungpinang City.